Alpha2 adrenoceptors regulate proliferation of human intestinal epithelial cells. (1st August 2000) - Schaak, S; Cussac, D; Cayla, C; Devedjian, J C; Guyot, R; Paris, H; Denis, C
Abstract : BACKGROUND AND AIMS: Previous studies on rodents have suggested that catecholamines stimulate proliferation of the intestinal epithelium through activation of α2 adrenoceptors located on crypt cells. The occurrence of this effect awaits demonstration in humans and the molecular mechanisms involved have not yet been elucidated. Here, we examined the effect of α2 agonists on a clone of Caco2 cells expressing the human α2A adrenoceptor. METHODS: Cells were transfected with a bicistronic plasmid containing the α2C10 and neomycin phosphotransferase genes. G418 resistant clones were assayed for receptor expression using radioligand binding. Receptor functionality was assessed by testing its ability to couple Gi proteins and to inhibit cAMP production. Mitogen activated protein kinase (MAPK) phosphorylation was followed by western blot, and cell proliferation was estimated by measuring protein and DNA content. RESULTS: Permanent transfection of Caco2 cells allowed us to obtain a clone (Caco2-3B) expressing α2A adrenoceptors at a density similar to that found in normal human intestinal epithelium. Caco2-3B retained morphological features and brush border enzyme expression characteristic of enterocytic differentiation. The receptor was coupled to Gi2/Gi3 proteins and its stimulation caused marked diminution of forskolin induced cAMP production. Treatment of Caco2-3B with UK14304 (α2 agonist) induced a rapid increase in the phosphorylation state of MAPK, extracellular regulated protein kinase 1 (Erk1), and 2 (Erk2). This event was totally abolished in pertussis toxin treated cells and in the presence of kinase inhibitors (genistein or PD98059). It was unaffected by protein kinase C downregulation but correlated with a transient increase in Shc tyrosine phosphorylation. Finally, sustained exposure of Caco2-3B to UK14304 resulted in modest but significant acceleration of cell proliferation. None of these effects was observed in the parental cell line Caco2. CONCLUSION: The results obtained in the present study support a regulatory role for α2 adrenoceptors in intestinal cell proliferation.